Implementasi Pemasaran Pendidikan Melalui Media Sosial Dalam Meningkatkan Mutu Pelayanan di SMKN 1 Sampang - Munib Munib; Abdullah Sarif; Fahestin Lailatul Aini (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2022)
Abstract In the current era of globalization, in the world of education there is competition between one institution and another. then the implementation of social media here has a strong influence on the marketing of educational services. based on these. So there are three research focuses that are the main studies in this research, namely: first, how is the planning of education marketing at SMKN 1 Sampang?. Second, how is the implementation of education marketing through social media at SMKN 1 Sampang?. third, how is the education service at SMKN 1 Sampang?. This research method uses a descriptive qualitative approach. The sources of data obtained are through interviews, observation, and documentation. The informants were the principal, vice public relations officer, head of administration, teachers, active students, alumni of SMK 1 students. The results showed that: first, at smkn 1 Sampang had planned to do marketing through social media with this the principal held a coordination meeting with stakeholders and also waka waka who have school programs. The planning is in order to optimize marketing activities to be more effective and efficient, this is in accordance with (playning organizing). Second, Smkn 1 Sampang has been marketing through social media including the media used in marketing Smkn 1 Sampang are Instagram, YouTube, Tiktok, Facebook, Twitter, and also websites such as websites.